Potential role of probiotic species in ameliorating oxidative stress, effect on liver profile and hormones in male albino rat model. (May 2021) - Anwar, Haseeb; Hussain, Ghulam; Rasul, Azhar; Ali Shah, Syed Muhammad; Naqvi, Syed Ali Raza; Bukhari, Shazia Anwer; Sohail, Muhammad Umar; Faisal, Muhammad Naeem; Mustafa, Imtiaz; Munir, Naveed; Nisar, Jaweria; Shaukat, Arslaan; et al.
Probiotics are living micro-organism preparations which can vigorously inhibit the probable pathogens colonization in the gut microbial ecology. Current experiment was designed to investigate the efficacy of imported probiotic species compared with the indigenous probiotics species on the oxidative stress, enzymes, and hormones in animal model. Thirty Albino rats were equally divided into three groups with 10 rats ( n = 10) in each group as Control (C), supplemented with imported probiotic species (IP), and supplemented with indigenous probiotics species (InP) for 21 days under controlled environment. The evaluation of treatments was done by testing the serum oxidative stress markers, liver enzymes (Aspartate transaminase and Alanine aminotransferase), lipid profile, and hormonal dynamics including Lutinizing hormone (LH), follicular stimulating hormone (FSH), and growth hormone (GH) in albino male rats. Results revealed that use of indigenous probiotic species significantly ( p < 0.05) reduces the oxidative stress and improves the antioxidant capacity; liver enzymes, total cholesterol, and LDL-Cholesterol were also reduced significantly ( p < 0.05) in InP as compared to IP group. Moreover, results of hormones including LH, FSH, and GH explored that indigenous probiotics have significant ( p < 0.05) potential to improve these hormones as compared to imported probiotics. Although, it could be concluded that InP have beneficial role in preventing the body from oxidative stress as well as in improving the blood parameters but comprehensive studies are required to investigate the detail gut ecology of the indigenous species which will definitely a strong support in preparing a more suitable local probiotic supplement.